Adaptive multi-rate video transcoding method - Fadlallah, Fadlallah Ali; Khalifa, Othman Omran (gtia.co.in Inc(Regd), 2014)
In this paper, we propose a multiple-transcoding tree (MTt) based on video streaming to deliver smooth and continuous flow of audio visual information to multiple-users with a different quality requirement. MTt, exploit the user terminal devices to transcode videos and forward to other devices. In MTt, each user determines a video quality requirement according to his/her environment capability: bandwidth, resolution, memory, processing, decoding, etc. Alone MTt transcoding tree, each receiver can receives video with specified quality.